Development of School Center of Excellence (SCE) program to realize literacy and numeracy-friendly school standards - H. Hamdani; Reni Marlina (Research and Development in Education (RaDEn), 2025)
The School Center of Excellence (SCE) program is the development of schools with certain expertise competencies. One of the important abilities that every Indonesia student must have is literacy and numeracy. The purpose of this study is to develop a literacy and numeracy friendly SCE program framework as a center of excellence. This program development uses the research and development (R&D) method with the ADDIE design. Based on the results of the analysis, it was found that the development of a literacy and numeracy friendly SCE program effectively develops students' literacy and numeracy according to the demands of 21st century competencies. Student responses to the development of literacy and numeracy friendly school programs are in the very good criteria. These criteria indicate that the school program as a center of excellence has a positive impact on students' needs and development and increases school awareness to play an active role in supporting literacy and numeracy. The implications of this research are in the form of a framework that can be a reference for governments in developing countries such as Indonesia to serve as a guide in developing literacy and numeracy friendly schools.